Analisis Lokasi dan Fasilitas Apartemen Kalibata City serta Implikasinya Terhadap Harga Jual dan Harga Sewa yang Ditawarkan - Radinda Nurbonita; Ragil Haryanto (Teknik PWK (Perencanaan Wilayah Kota), 2017)
The high population growth in Jakarta is causing the land increasingly limited with higher price. Based on that, some efforts are needed to maximize the limited land with every possible way, one of which is a vertical housing concept. In 2006, this concept is supported by a Government which is known as 1000 Tower Vertical Housing Program in the term of subsidized apartment. One of apartment in Jakarta that participated in that program is Kalibata City. Kalibata City is located in a very strategic location and close to the city center and has a very complete fasilities. But Kalibata City come with a relatively low prices compared with other subsidized apartment in Jakarta. Under these conditions, this study discusses about how are the characteristics of location and facilities of Kalibata City and their implications on the sale and rent prices. This study used quantitative approaches and methods. Quantitative method used in the research data in the form of figures and statistical analysis to testing the hypothesis. Kalibata City is located quite close to urban centers or the Central Business District (CBD) Jakarta. From the analysis, the overall average revenue Kalibata City dwellers belong to medium-rate, based on that majority of respondents said that the selection priority to choose the residence based one location aspect. Location Apartment Kalibata City located and have high accessibility because they have the time and travel costs low so as to provide time efficiency and ease of mobility for residents. Additionally, Apartment Kalibata City has been able to provide social facilities in residential environment to meet the various needs of its inhabitants, it is evidenced by the high level of occupant desires to use the facilities available.